Ekonomi Kreatif, Keterlibatan Stakeholder, dan Partisipasi Masyarakat Terhadap Sustainable ecotourism Ekowisata Mangrove Lembung Pamekasan - Maghfiroh, Hikmatul; Islam, Darul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Tourism has the potential to enhance a country's economy, but it also brings negative impacts associated with the industry. To address these issues, the concept of ecotourism was developed, in line with the principles of sustainable tourism development, with environmental preservation as its key focus. The aim of this study is to analyze the various factors influencing the evolution of sustainable ecotourism in the Mangrove Lembung area of Pamekasan, including the creative economy, stakeholder involvement, and community participation. The population for this study consists of 1,486 residents of Lembung Village, Pamekasan. Using the Slovin formula, the sample size was determined to be 94, and purposive sampling was applied for sample selection. Data was collected through questionnaires using a likert scale. The research findings indicate that the creative economy, stakeholder involvement, and community participation have a positive impact on the sustainability of Mangrove Lembung ecotourism in Pamekasan. The creative economy contributes to increasing the appeal of tourism through innovation in local products, while stakeholder involvement strengthens collaboration between institutions to preserve the environment. Community participation is also crucial in supporting the management of sustainable ecotourism, as the community plays a key role in the implementation of policies.